A conceptual meta-framework for managing multicultural global virtual teams. (1st January 2013) - Hosseini, M. Reza; Zuo, Jian; Chileshe, Nicholas; Baroudi, Bassam
Although GVTs can bring about many benefits for organisations, the potential advantages of using GVTs largely depend upon fulfilling the requirements prescribed by the critical success factors (CSFs) of implementing GVTs such as resolving the multiculturalism issues. Likewise, it is acknowledged that management aspects of implementing GVTs present one of the most complicated tasks in deploying the foregoing teams in organisations. These complications have roots in the necessity of using ICTs as the main medium exacerbated by multiculturalism and geographical dispersion of members. The area is in need of further research, which necessitates building intermediate theories and frameworks. This paper aims at critically observing and analysing the existing literature on managing GVTs as the first step resulting in developing theoretical frameworks. Drawing upon a dynamic integrated approach, this paper presents a conceptual meta-framework for incorporating different issues of managing GVTs titled as 'Dynamic Package of Managing' (DPM) global virtual teams.